2006
DOI: 10.1093/0199250960.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Ignorance of Language

Abstract: Is Chomsky right about the psychological reality of language? What is linguistics about? What role should linguistic intuitions play in constructing grammars? What is innate about language? Is there “a language faculty”? The book gives controversial answers to such questions: that linguistics is about linguistic reality and not part of psychology; that linguistic rules are not represented in the mind; that speakers are largely ignorant of their language; that speakers’ intuitions do not reflect information sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(76 citation statements)
references
References 130 publications
0
73
0
3
Order By: Relevance
“…Conjoining the alternative instruction with the actual instruction (cf. Devitt [2006b], p. 109) might have blocked such cases, but without affecting judgments based on personal preference.…”
mentioning
confidence: 99%
“…Conjoining the alternative instruction with the actual instruction (cf. Devitt [2006b], p. 109) might have blocked such cases, but without affecting judgments based on personal preference.…”
mentioning
confidence: 99%
“…For instance, it has been found that successful ball fielders run 'at a speed that kept the acceleration of the tangent of the angle of elevation of gaze to the ball at 0' (McLeod and Dienes, [1996], p. 531); see also the discussion in Devitt ([2006a], p. 50). This is not, however, grounds for attributing TANGENT OF AN ANGLE to the players: its applications are quite circumscribed to the area of ball-catching, and being a competent fielder typically does not influence learning and performance in trigonometry or in any other applications that depart significantly from fielding.…”
Section: Domain Crossing and Tacit Conceptsmentioning
confidence: 99%
“…The techniques and methodology which came along with the movement claimed to place the study of language at the level of an empirical, naturalistic science which would eventually be subsumed by biology or neurophysiology. Since this time, arguments have been proffered which challenged this claim on ontological grounds (Katz 1981;Carr 1990;Katz and Postal 1991), methodological grounds (Soames 1984;Hintikka 1999;Devitt 2006) and linguistic grounds from the various competing frameworks, some of which were spawned from the initial generative approach (Pustejovsky 1995;Prince andSmolensky 1993/2004;Kempson et al 2001;Jackendoff 2002).…”
Section: Introductionmentioning
confidence: 99%